Chemotaxis induced Turing bifurcation in a partly diffusive bacterial and viral diseases propagation model. (February 2020) - Tang, Xiaosong; Li, Jinzhong
Abstract: In this paper, we investigate a partly diffusive bacterial and viral diseases propagation model with chemotaxis subject to the homogeneous Neumann boundary condition. Choosing chemotaxis coefficient as bifurcation parameter, we discuss the stability of the positive equilibrium and the existence of Turing bifurcations by analyzing the corresponding characteristic equation. Based on the obtained results, we reveal the fact that chemotaxis can induce Turing bifurcations and the model has no Turing bifurcations when the chemotaxis is absent. Finally, some numerical simulations are also carried out to illustrate and expand the theoretical results.